New anti-cancer chemicals Ertredin and its derivatives, regulate oxidative phosphorylation and glycolysis and suppress sphere formation in vitro and tumor growth in EGFRvIII-transformed cells. Issue 1 (December 2016) - Atsumi, Sonoko; Nosaka, Chisato; Adachi, Hayamitsu; Kimura, Tomoyuki; Kobayashi, Yoshihiko; Takada, Hisashi; Watanabe, Takumi; Ohba, Shun-ichi; Inoue, Hiroyuki; Kawada, Manabu; Shibasaki, Masakatsu; Shibuya, Masabumi
Abstract Background EGFRvIII is a mutant form of the epidermal growth factor receptor gene(EGFR) that lacks exons 2–7. The resulting protein does not bind to ligands and is constitutively activated. The expression ofEGFRvIII is likely confined to various types of cancer, particularly glioblastomas. Although an anti-EGFRvIII vaccine is of great interest, low-molecular-weight substances are needed to obtain better therapeutic efficacy. Thus, the purpose of this study is to identify low molecular weight substances that can suppress EGFRvIII-dependent transformation. Methods We constructed a new throughput screening system and searched for substances that decreased cell survival of NIH3T3/EGFRvIII spheres under 3-dimensional (3D)-culture conditions, but retained normal NIH3T3 cell growth under 2D-culture conditions. In vivo activity was examined using a mouse transplantation model, and derivatives were chemically synthesized. Functional characterization of the candidate molecules was investigated using an EGFR kinase assay, immunoprecipitation, western blotting, microarray analysis, quantitative polymerase chain reaction analysis, and measurement of lactate and ATP synthesis. Results In the course of screening 30, 000 substances, a reagent, "Ertredin" was found to inhibit anchorage-independent 3D growth of sphere-forming cells transfected withEGFRvIII cDNA. Ertredin also inhibited sphere formation in cells expressing wild-typeEGFR in the presence of EGF. However, it did not affect anchorage-dependent 2D growth of parental NIH3T3 cells. The 3D-growth-inhibitory activity of some derivatives, including those with new structures, was similar to Ertredin. Furthermore, we demonstrated that Ertredin suppressed tumor growth in an allograft transplantation mouse model injected withEGFRvIII - or wild-typeEGFR -expressing cells; a clear toxicity to host animals was not observed. Functional characterization of Ertredin in cells expressingEGFRvIII indicated that it stimulated EGFRvIII ubiquitination, suppressed both oxidative phosphorylation and glycolysis under 3D conditions, and promoted cell apoptosis. Conclusion We developed a high throughput screening method based on anchorage-independent sphere formation induced byEGFRvIII -dependent transformation. In the course of screening, we identified Ertredin, which inhibited anchorage-independent 3D growth and tumor formation in nude mice. Functional analysis suggests that Ertredin suppresses both mitochondrial oxidative phosphorylation and cytosolic glycolysis in addition to promoting EGFRvIII degradation, and stimulates apoptosis in sphere-forming, EGFRvIII-overexpressing cells.